1997
DOI: 10.1542/peds.100.6.977
|View full text |Cite
|
Sign up to set email alerts
|

Effective Prophylactic Therapy for Cyclic Vomiting Syndrome in Children Using Amitriptyline or Cyproheptadine

Abstract: The antimigraine prophylactic drugs, amitriptyline and cyproheptadine, represent effective prophylactic agents for the management of CVS in the vast majority of patients fulfilling the diagnostic criteria for this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 17 publications
1
70
0
5
Order By: Relevance
“…In abdominal migraine, though the predominant symptom is abdominal pain; whereas in cyclic vomiting, the predominant symptom is the vomiting 16 . Patients with high frequency and greater severity of symptoms may benefit from prophylaxis with antimigraine medications, such as TCA, cyproheptadine, and propranolol 4,5 . Sumatriptan is a 5HT 1D1B agonist, FDA approved for acute treatment of migraine headaches in adults.…”
Section: Migraine/sumatriptanmentioning
confidence: 99%
See 1 more Smart Citation
“…In abdominal migraine, though the predominant symptom is abdominal pain; whereas in cyclic vomiting, the predominant symptom is the vomiting 16 . Patients with high frequency and greater severity of symptoms may benefit from prophylaxis with antimigraine medications, such as TCA, cyproheptadine, and propranolol 4,5 . Sumatriptan is a 5HT 1D1B agonist, FDA approved for acute treatment of migraine headaches in adults.…”
Section: Migraine/sumatriptanmentioning
confidence: 99%
“…However, it also occurs in adults and often goes undiagnosed for years due to a general lack of knowledge and understanding of the condition among physicians [1][2][3] . Treatment of patients depends on the frequency and severity of the vomiting episodes and may include the following: 1) prophylactic medications and 2) medications to help abort an episode 4,5 . Based on small case series, experts recommend sumatriptan during early stages of vomiting in children with cyclic vomiting syndrome 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been three reports [14][15][16] of children (n = 65) who received cyproheptadine for CVS. Response rates ranged from 40% to 83%.…”
Section: Cyclic Vomiting Syndromementioning
confidence: 99%
“…8 Its efficacy in children with FAP has been reported in a double-blind, placebo-controlled trial, 9 as well as in retrospective studies for treatment of FAP, FD, IBS, and AM. [10][11][12][13][14][15][16] 5-HT is a polyfunctional signaling molecule that serves as a paracrine factor, endocrine hormone, neurotransmitter, and growth factor. 17 Various 5-HT receptor subtypes regulate gut motility, secretion, and visceral sensitivity.…”
mentioning
confidence: 99%
“…Tricyclic antidepressants (TCAs) have been reported to be effective as prophylactic agents in children with CVS. 12 An open-label treatment group of 17 adult patients with CVS noted that 17% of patients had a complete remission with TCA therapy and almost 60% had a partial response. 3 More recently, a retrospective case series of patients who had failed TCAs as maintenance therapy reported that 15 out of the 20 patients studied had improvement in the frequency of their vomiting episodes with the newer antiepileptic drugs zonisamide and levetiracem.…”
mentioning
confidence: 99%